Mohd Kamal Hassan embodies integration of knowledge - Hasan, Md. Mahmudul (2020)
Educational philosopher Syed Muhammad Naquib al-Attas (1931-) is Malaysia's gift to the world of knowledge and learning. Through the concept of Islamisation/dewesternization of knowledge that he articulates in his monumental book Islam and Secularism (1978), he participates in the debate on the problems of education and contributes to the discourse of addressing them. Al-Attas emphasises the importance of producing a well-balanced personality through integration of knowledge. In this essay, I will discuss another contemporary Malaysian educational philosopher, Mohd. Kamal Hassan (1942-), who I believe embodies the concept of integration of knowledge.